On the origin of tellurium corrosion resistance of hot-rolled GH3535 alloy. (1st July 2020) - Wu, Bo-Heng; Jiang, Li; Ye, Xiang-Xi; Li, Chao-Wen; Liang, Jian-Ping; Liu, Fang; Li, Zhi-Jun
Highlights: Hot-rolled specimens possess the more Cr3 Te4 and MnTe in the scales. Te tends to be trapped by the primary M6 C carbides to form flake-like Cr3 Te4 . Hot-rolled specimens possess the shallower and fewer Te penetration and cracks. Abstract: The tellurium (Te) corrosion behaviors of the hot-rolled GH3535 alloy have been investigated systematically in this study as compared with the standard solid-solution treated one. In the hot-rolled alloy, the higher proportion of Cr3 Te4 and MnTe can be observed in the corrosion scales. Beneath the scales, Te was found to enrich in the primary M6 C carbides rather than at the grain boundaries. The blocking effect by the protective Cr3 Te4 and MnTe and the trapping effect by the primary M6 C carbides jointly contribute to the better Te corrosion and cracking resistance of the hot-rolled alloy.